Application of Thermo Electric Cooler (TEC) as a Low Cost and Environmentally Friendly Technology in Air Conditioning Systems - Heri Kusnadi; Ojak Abdul Rozak; Juhana; Mukhlis Hardiansyah (Jurnal Rekayasa Sistem & Industri, 2024)
The use of environmentally unfriendly chemicals (refrigerants) in Air Conditioners (AC) can damage theozone layer in the earth's atmosphere which has an impact on global warming. Therefore, an environmentallyfriendly cooling system is needed in the application of the Thermo Electric Cooler (TEC) cooling moduletechnology. TEC when supplied with DC voltage (direct current) one side will become hot, while the otherside will be cold, to maximize the cooling process, the hot side of TEC must be lowered as low as possibleby using a fan, heatsink and thermal paste (thermal grease). Using 6 pieces of TEC 12 V 6A, dimensions 40x 40 mm and 4 mm thick. TECs are arranged in parallel and electricity is arranged in series. TEC when thepower supply is connected to an electric current source, operating the 6 TECs attached to the heatsinkarranged in parallel and in series will cause one side to cool down (heat absorbed) and the other side tobecome hot (heat released). What causes the cold side of TEC to cool is the flow of electrons from a higherenergy level to a lower energy level. To find out the temperature of the Peltier cold results using a DHT22sensor with an Arduino microcontroller with a programmed temperature that automatically turns off and on.For the breaker or automatic switch using a 5-volt relay. the use of air conditioners per day (6 hours) issubject to tariffs Rp. 3,212 and the use of air conditioners for a month (30 days) every day the use of 6 hoursis subject to tariffs Rp. 96,360, so as to enjoy a safe and comfortable atmosphere by using environmentallyfriendly and low-cost technology.